The Potential Diuretic Comparison Between Parts Of Cucumber (Cucumis Sativus L.) In Male Mus Musculus - Vincensa, Elicia; Tjipto, Bambang W; Novita, Bernadette D (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
ntroduction : Cardiovascular diseases are one of the most common cause of death inIndonesia. One kind of cardiovascular event is hypertension. Hypertension is a type ofCardiovascular Disease which incidence rate is predicted to increase in the year of 2025.Diuretic is one of the therapies that can be used for this disease. Diuretic works by decreasingblood volume by managing water and sodium balance inside the body. This effect can beobtained from Cucumber (Cucumis sativus L.). Purpose : The aim of this study is to explain the differences in potential diuretic effect amongparts of Cucumber (Cucumis sativus L.). Method : This study use post-test only control group design method in animal subject(invivo). Animal subjects in this study were 44 male Mus musculus. the animals were dividedinto 9 treatment groups and 2 control groups. All Mus musculus get 1 mL methanol extract ofCucumber (Cucumis sativus L.) according to their group. The animals were put in metaboliccage to measure urine volume for 24 hours. Results : Part of Cucumber (Cucumis sativus L.) that has the best potential diuretic were theflesh and rind on 0,5 mg/mL. Part of Cucumber (Cucumis sativus L.) that has the highestnatriuresis and kaliuresis was whole fruit (flesh, rind, and seed). Conclusion : Cucumber (Cucumis sativus L.) has a similar potential diuretic with Furosemid.Low concentrations lead to better potential diuretic. Natriuresis and Kaliuresis can also befound on Cucumber (Cucumis sativus L.).